MSCs promote the development and improve the function of neonatal porcine islet grafts. Issue 6 (18th January 2018) - He, Sirong; Wang, Chengshi; Du, Xiaojiong; Chen, Younan; Zhao, Jiuming; Tian, Bole; Lu, Huimin; Zhang, Yi; Liu, Jingping; Yang, Guang; Li, Lan; Li, Hongxia; et al.
ABSTRACT: Deficient insulin secretion caused by immaturity is the predominant disadvantage of neonatal porcine islets (NPIs) when they serve as a source for islet xenotransplantation. We hypothesize that the transplantation of NPIs with a combination of mesenchymal stem cells (MSCs) can accelerate NPI maturation and improve the engraftment and function of NPIs. After indirect coculturing with monkey MSCs over 21 d, insulin secretion and the expression of regulatory genes relevant to development were assessed in NPIs. NPIs alone or in combination with allogeneic MSCs were intraportally transplanted into diabetic monkeys. Glycemic control was monitored, and graft function was evaluated. Our results suggest that MSCs benefit both the development and proliferation of NPIs in the coexisting systems in vitro and in vivo. These effects are dependent on platelet‐derived growth factor receptor‐a and are relevant to the inhibition of downstream target Notch1 signaling and the activation of PI3K/protein kinase B signaling.—He, S., Wang, C., Du, X., Chen, Y., Zhao, J., Tian, B., Lu, H., Zhang, Y., Liu, J., Yang, G., Li, L., Li, H., Cheng, J., Lu, Y. MSCs promote the development and improve the function of neonatal porcine islet grafts. FASEB J. 32, 3242–3253 (2018). www.fasebj.org